In vitro and in vivo impact assessment of eco-designed CuO nanoparticles on non-target aquatic photoautotrophic organisms - Pontes, Montcharles S.; Graciano, Daniela E.; Antunes, Débora R. [UNESP]; Santos, Jaqueline S.; Arruda, Gilberto J.; Botero, Eriton R.; Grillo, Renato [UNESP]; Lima, Sandro M.; Andrade, Luís H.C.; Caires, Anderson R.L.; Santiago, Etenaldo F. (Elsevier, 2020)
This work has assessed the impact of copper oxide nanoparticles (CuONPs), designed via green route, toward photosynthetic apparatus on aquatic photoautotrophic organisms. In order to filling knowledge gaps, in vitro and in vivo assays were performed, using cyanobacterial phycocyanin (C-PC) from Arthrospira platensis and Lemna valdiviana plants (duckweed), respectively. Impairment in light energy transfer became evident in C-PC exposed to CuONPs, giving rise to an increase of light absorption and a suppression of fluorescence emission. Fourier transform infrared spectroscopy (FTIR) results showed that C-PC structures might be altered by the nanoparticles, also revealed that CuONPs preferably interacts with -NH functional groups. The data also revealed that CuONPs affected the chlorophyll a content in duckweed leaves. In addition, photosystem II (PSII) performance was significantly affected by CuONPs, negatively impacting the PSII photochemical network. In summary, the results point out that, even eco-friendly designed, CuONPs may negatively affect the photosynthetic process when accumulated by aquatic photoautotrophs.
Keywords: CuO nanoparticle; Cyanobacterial phycobiliprotein; Duckweed; Environmental risk; Green synthesis; Photoautotrophic organism